Kajian Awal Fungsi Gua dan Wilayah Sebaran Situs Gua di Maluku dan Maluku Utara - Syahruddin Mansyur (Kapata Arkeologi, 2007)
Cave Exploiting tradition have been started since a period Plestocen For till A period of Holocen. In Indonesia, cave sites present cultural footstep in the form of rock art, appliance petrify, kitchen garbage, construct human being, pottery and ceramic. The Cave sites of quite a lot found in North Moluccas and Moluccas presentedly is very finding vary. Data presented by each site give indication of early about function of cave. That way things of distribution map around. This article try to give picture of early function of cave pursuant to its finding and regional map distribution and also early asessment whereas cultural current, both for coming from Asia (west) and  also from Australian or Pacifik (East).